(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In this article the differences between information and knowledge are identified,and how these concepts are properly implemented by industrial firms in the Sundsvall region. An important goal of this empiric investigation was to find out if these companies have specific processes to dinamize the flow and exchange of knowledge and information, and if they would be eager to share knowledge and information with other companies. From the information gathered, we decided to find out whether the generation and use of information and knowledge is important,and up to what level.